La dynamique d’enfrichement, ses expressions paysagères et ses significations : le cas du Beaujolais viticole - Jessica Pic; Yoann Le Guen; Étienne Cossart; Mathieu Fressard (VertigO)
The economic crisis that affects the Beaujolais vineyard since the late 1990s is the origin of the abandonment of previously vine-growing plots. It implies important landscape mutations, worrying the local stakeholders. The lack of definition of these abandoned plots, as well as the technical difficulty to qualify and quantify the conversion dynamics, is a problem to hold back the conversion from agricultural to abandoned plots. Photo-interpretation combined with fieldwork and interviews of stakeholders was conducted to characterize the extension and spatial patterns of abandoned plots. It was done for three catchments to compare the results and highlight the underlying ways and means of the conversion of vine into abandoned plots. A typology was built : it includes six types of abandoned plots, each one having, according to its features, its own impact on the landscape. Three temporal filiations between the types were identified : one is located on the hillside, one is in the plain, but the previous vine stocks have been uprooted, and one is in the plain and the vine stocks have not been uprooted. The conversion into abandoned plots was quantified and related with the vine plots extent of the catchments in 1999 : 1.5 % of the vine plots surface that has been converted into abandoned plots for the Lower Ardières catchment, 8.4 % for the Marverand catchment and 8.7 % for the Merloux catchment. A distinction between north and south Beaujolais has been noticed, highlighting the slope and the vintage sorting influence on the abandonment but also of land withholding phenomena.